The relationship between risk management strategies and the risks of container transport: Applied research in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to find out the nature of the relationship between the interrelationships and the interrelationships between risk management strategies (avoiding danger, risk exposure, risk exhibition, preventive programs and activities to reduce risks) and the dangers of container transportation, as an independent variable in the dangers of container transportation as a dependent variable, the study started from the problem that the company suffers from The practical aspect of the study was applied at the National Insurance Corporation, and the researcher designed a diagram according to the study's schematic diagram. The study, and for the purpose of data and information related to that, it relied on the descriptive analytical method, and it was used The questionnaire to explore the opinions of the research sample, which consisted of (General Director, Associate Director General, Department Manager, Associate Department Director, Division Officer, Unit Officer), which numbered (69) individuals, and then analyzed the results of the research sample’s answers through the (SPSS) program and according to the Statistical methods, and the research reached a number of results, most notably: There is a weakness in the training programs to train employees and develop their skills to understand risk management.